The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/lary.29691
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Tinnitus Development Due to Stress: An Experimental Study in Rats

Abstract: Objectives/Hypothesis: Tinnitus can develop due to, or be aggravated by, stress in a rat model. To investigate stress as a possible causal factor in the development of tinnitus, we designed an animal study that included tinnitus behavior and excitatory/inhibitory neurotransmitter expression after noise exposure as well as restraint stress.Study Design: An experimental animal study. Methods: Wistar rats were grouped according to single or double exposure to noise and restraint stress. The noise exposure (NE) gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Though these findings do not directly correlate with tinnitus, the association with hearing loss and interaction with the auditory cortex, respectively, suggests an underlying mechanism with tinnitus onset. An experimental study evaluating whether tinnitus can develop due to, or be aggravated by stress, in rats, found reduced gap prepulse inhibition of the acoustic startle (GPIAS) reflex, a reliable indicator of tinnitus development in animals ( Kim et al, 2021 ). The study also reported decreased immunofluorescence expression of GABA A receptor α1 and increased NMDA receptor 1 immunofluorescence expression in the hippocampus in the group exposed to both noise and stress.…”
Section: Stress and Tinnitusmentioning
confidence: 99%
See 1 more Smart Citation
“…Though these findings do not directly correlate with tinnitus, the association with hearing loss and interaction with the auditory cortex, respectively, suggests an underlying mechanism with tinnitus onset. An experimental study evaluating whether tinnitus can develop due to, or be aggravated by stress, in rats, found reduced gap prepulse inhibition of the acoustic startle (GPIAS) reflex, a reliable indicator of tinnitus development in animals ( Kim et al, 2021 ). The study also reported decreased immunofluorescence expression of GABA A receptor α1 and increased NMDA receptor 1 immunofluorescence expression in the hippocampus in the group exposed to both noise and stress.…”
Section: Stress and Tinnitusmentioning
confidence: 99%
“…The study also reported decreased immunofluorescence expression of GABA A receptor α1 and increased NMDA receptor 1 immunofluorescence expression in the hippocampus in the group exposed to both noise and stress. This suggests an imbalance in excitatory and inhibitory neurotransmitters in the hippocampus to be the mechanism responsible ( Kim et al, 2021 ). The inferior colliculus is also affected by stress where atrophy of the inferior colliculus in rat brains was reported by a study assessing the effect of chronic immobilization stress isolation in the auditory and visual regions ( Dagnino-Subiabre et al, 2005 ).…”
Section: Stress and Tinnitusmentioning
confidence: 99%
“…This method is much faster, allows to separate tinnitus-positive from tinnitus-negative animals and can also be used by scientists with little experience in animal behavior [53]. At the moment, despite some limitations, several studies have used the GPIAS test and have led to significant findings in tinnitus research [54][55][56].…”
Section: Introductionmentioning
confidence: 99%